2015
DOI: 10.11606/issn.1678-4456.v52i3p266-272
|View full text |Cite
|
Sign up to set email alerts
|

Influência das fases de anestro e diestro na competência meiótica oocitária de cadelas

Abstract: <p>A cadela apresenta particularidades reprodutivas que a diferencia de outras espécies. Diversos experimentos têm sido realizados visando estabelecer protocolos eficientes para a maturação, entretanto os resultados mostram-se insatisfatórios. Nesse aspecto, a fase reprodutiva da fêmea doadora deve ser considerada, já que pode ser um fator de variabilidade dos achados ate então presenciados nessa espécie. O objetivo deste estudo foi avaliar a influencia das fases do ciclo estral (anestro e diestro) na ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…The deletion of both HDAC1 or HDAC2 genes in mouse oocytes results in decreased ovary size, arrest of follicle development at the secondary follicle stage, and infertility. The absence these proteins in this study can be one of the factors responsible for the high percentage of oocytes that remain in the stage of germinal vesicle (GV) regardless of culture conditions observed in earlier studies (Pereira et al, 2013;Pereira, Bersano, & Lopes, 2015). (Pereira et al, 2013).…”
Section: Calcium/calmodulin-stimulated Protein Kinase II (Camkii) Ismentioning
confidence: 63%
“…The deletion of both HDAC1 or HDAC2 genes in mouse oocytes results in decreased ovary size, arrest of follicle development at the secondary follicle stage, and infertility. The absence these proteins in this study can be one of the factors responsible for the high percentage of oocytes that remain in the stage of germinal vesicle (GV) regardless of culture conditions observed in earlier studies (Pereira et al, 2013;Pereira, Bersano, & Lopes, 2015). (Pereira et al, 2013).…”
Section: Calcium/calmodulin-stimulated Protein Kinase II (Camkii) Ismentioning
confidence: 63%
“…Thus, oocytes from the anoestrous phase would have low potential to reach the M‐II stage due to lack of communication between cumulus cells and the oocyte. Pereira, Bersano, and Lopes () also observed that oocytes obtained from the dioestrous phase demonstrated greater meiotic competence since the chances of finding an oocyte at M‐II were 1.9 times greater in oocytes obtained from ovaries at the dioestrous phase when compared to the anoestrous phase. The fact that the p34 cdc2 protein is expressed more strongly in the nucleus of other mammalian species and in the periphery of the cytoplasm with less intense staining in the zona pellucida in bitches raises the hypothesis that factors transmitted via gap junctions may be influencing meiosis resumption.…”
Section: Discussionmentioning
confidence: 90%
“…In domestic mammals, with the removal of the oocyte from the follicular environment, there is spontaneous meiosis resumption. In domestic dogs, although meiosis resumption occurs, maturation rates are very low and the percentage of oocytes remaining in the germinal vesicle (GV) is highly significant (Pereira, Bersano, & Lopes, ). The molecular mechanisms responsible for meiosis activation and block have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, comparando-se os diferentes status reprodutivos, os oócitos obtidos da fase de diestro apresentaramse mais competentes meioticamente, fato este representado pelo maior índice de oócitos nos estágios de QVG e M-II (p<0,05). Esses dados corroboram os resultados observados em experimentos prévios, já que as chances de se encontrar um oócito no estágio de M-II foram 1,9 (1,04-3,46) vezes maiores em oócitos obtidos da fase de diestro (p<0,05) (4) . Um dos fatores responsáveis pelos oócitos obtidos da fase de diestro serem mais aptos a completarem a maturação pode ter sido pelo efeito das variações nas concentrações basais de gonadotrofinas, como ocorre em outras espécies.…”
Section: Discussionunclassified
“…Em cães domésticos, independente das condições de cultivo adotadas, a parcela de oócitos que permanecem no estágio de vesícula germinativa (VG) é alta. Os resultados não são promissores, apresentando índices de 0 a 58% para retomada da meiose e em média 20% para metáfase II (M-II) (2)(3)(4) . Na Medicina Veterinária, a MIV pode oferecer diferentes alternativas para preservar a fertilidade e diversidade genética de indivíduos de alto valor genético que falharam em se reproduzir naturalmente ou precisaram submeter-se a ovário-histerectomia devido a razões médicas e para a preservação de espécies ameaçadas de extinção (5) .…”
Section: Introductionunclassified